Tratamento ortodôntico lingual individualizado com o sistema Incognito - Martins, Isabela Parsekian; Martins, Renato Parsekian [UNESP]; Magno, Amanda Fahning [UNESP]; Araújo, Adriano Marotta [UNESP]; Martins, Lídia Parsekian [UNESP] (My University, 2012)
Introduction: The orthodontic treatment using lingual brackets has been desired by adult patients for esthetic factors. In this paper it is described the clinical steps of an orthodontic treatment using Incognito™ system, individualized lingual brackets and archwires designed by CAD/CAM technology. Methods: The presented case describes the treatment of a patient with mesofacial growth pattern,Class I malocclusion, with mandibular crowding and diastema between the upper central incisors, treated using 100% individualized lingual brackets. Results: After treatment, the molar relation of Class I was kept, the spaces between upper central incisors were closed and mandibular crowding corrected. Conclusion: This case report demonstrated the efficiency of the new method for lingual orthodontic treatment.

Introdução: a terapia ortodôntica com braquetes linguais tem sido procurada por pacientes adultos que optam pela estética durante o tratamento ortodôntico. Neste artigo está descrita a sequência clínica de tratamento ortodôntico lingual com o sistema Incognito™, braquetes linguais e arcos ortodônticos individualizados, produzidos com tecnologia CAD/CAM. Métodos: o caso clínico apresentado descreve o tratamento de um paciente adulto com padrão de crescimento mesofacial, portador de má oclusão Classe I, apresentando apinhamento inferior e diastemas interincisais superiores, tratado com braquetes linguais 100% individualizados. Resultados: ao final do tratamento, a relação molar de Classe I foi mantida, os espaços interincisais superiores foram fechados e o apinhamento inferior corrigido. Conclusão: o caso clínico apresentado demonstrou a eficiência do novo método de tratamento ortodôntico lingual.
Individualized lingual orthodontic treatment using incognito system
Keywords: Orthodontics; Corrective; Esthetics; Orthodontic appliances; Ortodontia corretiva; Estética; Aparelhos ortodônticos